Quantitative genetic analysis reveals potential to genetically improve fruit yield through selection in Solanum lycopersicum × Solanum pimpinellifolium crosses under humid condition - Chikezie Onuora Ene; Wosene Gebreselassie Abtew; Happiness Ogba Oselebe; Temesgen Matiwos Menamo; Friday Ugadu Ozi; Chibueze Kelechi Ene; Nnamdi Ogwo (Agrosystems, Geosciences & Environment)
Abstract Despite the enormous achievements recorded in tomato (Solanum lycopersicum L.) breeding using traditional and molecular approaches, most cultivars find humid environments highly unfavorable. As a result, fruit production cannot meet the rapidly increasing global demand. The objective of this study was to evaluate the adaptability of genotypes to humid conditions and estimate gene actions responsible for the inheritance of selected traits that improve tomato yield. Four crosses were made among five morphologically diverse parents: Wild parent—Solanum pimpinellifolium (LA2093) and S. lycopersicum—CLN2498D, CLN2417H, Tima, and UC Dan INDIA using wild parent as a common pollen donor. The generations of F1s, F2s, BC1s, and BC2s obtained were laid out in a repeated randomized complete block design with three replicates. The analysis of variance was estimated using a linear mixed model. The genetic effects were estimated using the Hayman model using the best linear unbiased prediction values. Significant differences in traits were observed among parental lines and their crosses. The wild parent exhibited superior performance in terms of total number of fruits per plant (TNFrPP, 467.19), number of fruits per truss (NFrPT, 11.1), and delayed fruit spoilage (D100FrSP, 34.45) compared to cultivated varieties. The highest TNFrPP (129.89) was achieved in the BC2 CLN2498D × Wild cross. Similarly, the highest NFrPT (10.67) was also observed in the BC2 CLN2498D × Wild cross. For D100FrSP, the BC2 CLN2417H × Wild cross showed a value of 33 days. Additive and additive–additive gene effects were significant for most of the fruit traits including the weight and yield of the fruit. Additive variation is important for improving tomato yield by selecting the best individuals from the F2 populations, since reliance on selective gains will only be on gametic variation. Advancement of the segregating populations would involve breeding methods such as single seed descent, pureline selection, pedigree, and gametic or backcross selections. In all generations, CLN2498D × Wild and UC Dan INDIA × Wild crosses expressed the best performance for all traits, including fruit yield. This makes them a good material for selection and exploitation in tomato breeding for increased fruit yield and adaptability to humid environments. These crosses can form a novel source of genetic improvement for future breeding.